'A girl is Arya Stark from Winterfell': The monomyth as a feminist journey in Game of Thrones. Issue 1 (1st June 2022) - Fernández-Morales, Marta; Menéndez-Menéndez, María Isabel
Joseph Campbell's The Hero with a Thousand Faces is a classic for the analysis of the archetypal hero's journey, and contemporary TV series use his monomyth to elaborate character profiles. Such is the case of the corpus of our work: Game of Thrones, the TV adaptation of George R. R. Martin's saga A Song of Ice and Fire. Amid the multiple relevant figures in Game of Thrones, this article takes Arya Stark as the object of study to discuss questions of representation and gender in contemporary TV. Our method comprises the close reading of Arya's narrative arc and our main unit of analysis is the gender variable, placed in an intersectional frame. We argue that Arya fits the nuclear structure of the monomyth, but also that she challenges its constrictions, pushes its limits and rewrites some of its elements to create a post-gender version of the Campbellian adventure. Through a succession of extremely intense experiences, Arya is the character that most painstakingly earns and most adamantly vindicates her self-constructed identity in Game of Thrones. Hers, we contend, is a feminist journey that has broken moulds in audio-visual narrative and left a deep trace in the history of contemporary television.